PENENTUAN STRATEGI DENGAN PENDEKATAN ANALISIS SWOT PADA HOTEL NONGSA POINT MARINA & RESORT DALAM MENGHADAPI PERSAINGAN BISNIS - Riszky Ramadhan Nourlette; Shinta Wahyu Hati (Inovbiz: Jurnal Inovasi Bisnis, 2017)
Abstract :This study aimed to determine the external and internal condition of Nongsa Point Marina & Resort Hotel as the basis of defining a strategy to face the competition. The method used in this study is qualitative descriptive approach.   Primary and secondary data is processed to gather information about  the  strengths  and  weaknesses  and  the  opportunities  and  threats  of Nongsa  Point  Marina  &  Resort  Hotel.  The  result  of  this  study  is  the competitive strategy which must be applied is market penetration. This result is obtained through a series of processes from SWOT Analysis which is started from analyzing the internal and external factors until defining a strategy with QSPM matrix. Keywords: Hotel, SWOT Analysis, QSPM Matrix